Disability, rurality and spatial competence: on the importance of embodied knowledge and supportive contexts - Susanne Stenbacka (Fennia: International Journal of Geography)
In this article, I investigate the interaction between the rural environment and disability to explore how place can be a resource in processes of participation and belonging. The aim is to explain how individuals experiencing disability make use of, give meaning to, evaluate, and negotiate their surroundings. The embodied experiences of individuals living in rural places are at the centre of the study that this work is based on. The empirical material includes in-depth interviews with 15 men and women experiencing either a physical or a neuropsychiatric impairment. The analysis focuses upon the environmental-social interface. The article argues that the concept of spatial competence offers a relatively open entrance for studying enabling spaces and identifying factors contributing to the well-being of individuals and places. Spatial competence is understood as a process that emphasises agency and the ability to navigate social and material environments. Departing from the participants’ elaborations and reflexivity with regard to their local places, I argue that the physical environment, social networks and local welfare structures constitute pillars in the development of spatial competence. Welfare structures are explicitly addressed, for example regarding social support in everyday life or material support in the case of remodelling a home. These structures are also implicitly present in narratives on excursions, outdoor activities or social contexts initiated or supported by the public sector or civil society. A conclusion is that the development of spatial competence intersects with a functioning welfare society.